2011
DOI: 10.2172/1004790
|View full text |Cite
|
Sign up to set email alerts
|

Gasoline from Wood via Integrated Gasification, Synthesis, and Methanol-to-Gasoline Technologies

Abstract: Executive SummaryThis report documents the National Renewable Energy Laboratory's (NREL's) assessment of the feasibility of making gasoline via the methanol-to-gasoline (MTG) route using syngas from a 2,000 dry metric tonne/day (2,205 U.S. ton/day) biomass-fed facility.The thermochemical route of biomass gasification produces a syngas rich in hydrogen and carbon monoxide. The syngas is then converted into methanol, and the methanol is converted to gasoline using the methanol-to-gasoline (MTG) process first dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 21 publications
0
89
0
Order By: Relevance
“…The collected and analyzed data reflect the world's demonstration and commercial gasification units having continuous layers. It is shown that wood gasification technology has achieved significant development at both laboratory and pilot levels [4,[6][7][8]; a number of demonstration and commercial plants operate, although the efficiency of wood gasification in a continuous layer to obtain high-energy synthesis gas remains an urgent problem.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…The collected and analyzed data reflect the world's demonstration and commercial gasification units having continuous layers. It is shown that wood gasification technology has achieved significant development at both laboratory and pilot levels [4,[6][7][8]; a number of demonstration and commercial plants operate, although the efficiency of wood gasification in a continuous layer to obtain high-energy synthesis gas remains an urgent problem.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…For tar and light hydrocarbon reforming some alternatives have been studied in previous BTL/G publications (SR, ATR and TR, used alone or in combination with removal systems for H 2 and CO 2 ) [15,16,[19][20][21][22][23][24][25][26][27][28]. In this work, three alternatives for syngas reforming are considered: SR, secondary reformer (secondary-ATR) and TR.…”
Section: Gas Clean-up and Conditioningmentioning
confidence: 99%
“…It can also be used as a feedstock (syngas) in the synthesis of chemicals such as methanol and fuel production [2,9,14,23], although it is noteworthy at this stage that there is no standard gasifier that is able to handle a wide range of biomass types, as a result of nonhomogeneous character of most biomass resources, which pose difficulties in maintaining constant feed rates to gasification units; therefore, there is the need for proper equipment design for the gasification process.…”
Section: Brief Overview Of Biomass Gasification Technologies and Typementioning
confidence: 99%
“…In addition, irrespective of the fact that the advanced countries are presently heavily reliant on fossil fuels, researchers in these countries are also optimising efforts in bioenergy-related researches (e.g., [2,9]), as biomass is estimated to be contributing in order of 10-14% of the world's power supply [10,11], with a likelihood of an increase in this contribution in the near future. The increasing research in and utilisation of bioenergy is partly in preparation for future unpredictability in supply, demand, and price of fossil fuels and associated products as a result 2 ISRN Renewable Energy of current increasing usage of these types of fuels and their supposed expected future finiteness [1,9,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation